Ismael Silva: uma memória feita de fragmentos e silêncios - Porto, Carla Lisboa [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Neste artigo farei uma reflexão sobre as peculiaridades da memória do compositor Ismael Ismael Silva (1905 – 1978), e de seus artifícios para valorizá-la. Pretendo discutir, a partir de reportagens, material iconográfico e entrevistas concedidas à imprensa, sobre suas ferramentas para a construção de sua imagem como sambista. Desse modo, surgem novas possibilidades de pesquisa sobre a construção de uma memória da música popular no Brasil.

In this exposition I think about the peculiarities of the composer Ismael Silva’s memory (1905 – 1978), and his skills to value it. I intend to discuss, focusing on the author’s reports, the iconographic material and interviews gave to the press, about his tools to build his image as a sambista. In this way, new possibilities of research about the construction of a memory of the popular music in Brazil appear.
Ismael Silva: a memory made with fragments and silences. Ismael Silva: a memory made with fragments and silences.
Keywords: Ismael Silva; popular music; popular music memory; Ismael Silva; música popular; memória da música popular